Gamifying English Proficiency: A Needs Analysis for EFL Student Course Design - Basthomi, Yazid; Ivone, Francisca Maria; Kharis, M.; Slamet, Joko (Online Learning, 2025)
This study addresses critical gaps in English proficiency assessments, particularly for English as a Foreign Language (EFL) students, by focusing on the foundational aspect of needs analysis in designing a platform to assist EFL students in preparation for real English proficiency tests. The existing tests, such as TOEFL and IELTS, often fail to align with the practical language skills necessary for test preparation. By conducting a needs analysis, this research aims to lay a robust foundation for the development of a gamified platform tailored to the specific linguistic demands of EFL learners. Employing a cross-sectional survey method, 120 participants from various academic levels were purposively selected from the Faculty of Letters at Universitas Negeri Malang. The findings reveal both positive and negative insights into learner preferences and goals, highlighting the importance of interactive learning experiences and practical application opportunities. The study underscores the transformative potential of gamification in language learning, emphasizing its ability to enhance learner engagement and motivation. The implications of the study extend to language educators, curriculum developers, and policymakers, advocating for the integration of learner-centred approaches and gamified elements into English proficiency courses. Recommendations include the development of tailored instructional materials and the implementation of innovative pedagogical strategies to address the diverse needs of EFL students effectively.